Socioeconomic inequalities and mental stress in individual and regional level: a twenty one cities study in China - Wang, Hongmei (Int J Equity Health, 2015)
OBJECTIVES: This study will examine explanatory variables including socioeconomic inequalities related to mental stress at both the individual and regional level. METHODOLOGY: A cross-sectional multistage sampling process was used to obtain participants. Data on mental stress and individual socioeconomic status were gathered via face to face interview. Regional variables were retrieved from a national database. Multilevel logistic regression analysis was used to assess socioeconomic variances in mental stress. RESULTS: Among the 16,866 participants, 27.2% reported severe levels of mental stress (95% CI: 19.4%-35.1%). Multilevel regression analysis indicated that lower individual educational attainment and income, and lower regional Per Capita GDP was associated with mental stress. The results also indicated that managers, clerks, and professional workers manifested higher stress levels than those in other occupations. CONCLUSIONS: Based on the results of this study individual and regional socioeconomic inequalities in China are associated with mental stress.